Rationality of the FIGO2023 staging for early-stage endometrial cancer, compared with the FIGO2009 staging - Yiqin Wang; Jianliu Wang; Xingchen Li; Aoxuan Zhu; Yangyang Dong (Gynecology and Obstetrics Clinical Medicine)
Objective The International Federation of Gynecology and Obstetrics (FIGO) released a new staging for endometrial cancer (EC), which revised the FIGO2009 staging to include histopathological and molecular features. The purpose of this study was to validate the prognostic accuracy of the new staging and discuss its clinical applicability.Methods In this single-centre retrospective study, 540 patients with primary surgically treated early-stage EC were enrolled and staged according to FIGO2009/2023. Kaplan-Meier survival analysis was used to compare for prognostic differentiation. Cox regression was used to identify potential prognostic indicators.Results A total of 81 patients underwent staging shifts, all stage elevation. The prognosis difference between new stages I and II was more significant. The new staging was more predictive of death postoperatively. Lesion maximum diameter (LMD) was one of the independent risk factors associated with prognosis. Taking LMD=5.70 cm as the cut-off value could further differentiate patients with divergent prognoses within FIGO2023 stage IIC.Conclusion FIGO2023 staging demonstrated greater prognostic accuracy. In addition, LMD may be another critical factor affecting prognosis.